Preparation of Activated Carbon from Hawthorn Core Stones by Chemical Activation - Saleem, Rami N.; Abduljabar, Payman Abdulsatar; Faraj, Samara S. (Science Journal of University of Zakho, 2022)
The objective of this study is the characterization of activated carbon prepared from hawthorn core natural residue which is a vegetation waste. By using zinc chloride (ZnCl2) as a chemical agent 40 % for 25 hours at (25 °C) as a raw material in this work. The best conditions were determined to be a carbonization temperature of 400 °C for 1 hour and a maximum yield is 82 % Different operational factors such as carbonization time and temperature were used to prepare activated carbon from hawthorn core stones, pH, ash content, density, humidity content, conductivity, iodine number, and methylene blue dye absorption were all investigated in the generated activated carbon. Characterization of the activated carbon obtained was performed by using scanning electron microscopy (SEM), X-ray diffraction (XRD) and energy dispersive X-ray (EDX). Finally, the activated carbon synthesized in this study has acquired good properties that enable it to play an important function in a variety of environmental applications, including eco-protection, water treatment, and wastewater treatment and it was compared to a commercial reference sample from the B. D. H Company in industrial applications.